Vehicle energy systems for autonomous driving - Goh, Daniel Jun Hao (Nanyang Technological University, 2020)
The Shell Eco-Marathon is an energy efficiency competition for students to design and build ultra-energy-efficient cars to compete against each other. The Nanyang Venture, which is the student team from the School of Mechanical and Aerospace Engineering (MAE) at the Nanyang Technological University (NTU) of Singapore, has been participating in the competition since 2009. In 2018, Shell added an autonomous category to the competition that requires the cars in competition to complete five challenges. In order to compete in this category, the autonomous capabilities have to be added to the Nanyang Venture 11 (NV11). NV11, which is an electric vehicle, participated in the Shell Eco-Marathon Asia 2019 in the efficiency category. This project aims to complete the development of the autonomous software of Nanyang Venture 11 as well as to integrate the entire autonomous system so that it can participate in the autonomous category of the Shell Eco-Marathon competition. This report details the work done on the development, implementation, and integration of the autonomous software with the rest of the system. Future work and recommendations to improve the autonomous capabilities are also provided.